48th AIAA Aerospace Sciences Meeting Including the New Horizons Forum and Aerospace Exposition 2010
DOI: 10.2514/6.2010-301
|View full text |Cite
|
Sign up to set email alerts
|

Fiber-Based Measurement of Bow-Shock Spectra for Reentry Flight Testing

Abstract: We demonstrated a fiber-based approach for obtaining optical spectra of a glowing bow shock in a high-enthalpy air flow. The work was performed in a ground test with the NASA Ames Aerodynamic Heating Facility (AHF) that is used for atmospheric reentry simulation. The method uses a commercial fiber optic that is embedded in the nose of an ablating bluntbody model and provides a line-of-sight view in the streamwise direction -directly upstream into the hot post-shock gas flow. Both phenolic impregnated carbon ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 15 publications
1
3
0
Order By: Relevance
“…Graybody assumption is common in pyrometric measurements on soot particles for the wavelength of interest. Previously, attempts have been made to predict the shock-layer temperature by fitting Planck's blackbody curve to the emission spectra obtained from the shock layer using fiber-based systems [22,23]. Emission spectroscopy performed in our shock tunnel also confirmed that the shock region majorly radiates as a continuous broadband source.…”
Section: Introductionsupporting
confidence: 53%
“…Graybody assumption is common in pyrometric measurements on soot particles for the wavelength of interest. Previously, attempts have been made to predict the shock-layer temperature by fitting Planck's blackbody curve to the emission spectra obtained from the shock layer using fiber-based systems [22,23]. Emission spectroscopy performed in our shock tunnel also confirmed that the shock region majorly radiates as a continuous broadband source.…”
Section: Introductionsupporting
confidence: 53%
“…This data is unlikely to come from a flight case, since even the Apollo 4 measurements at Lunar-return conditions did not contain enough ablation to influence the radiation significantly. The preliminary work by Schott et al 168 and D'Souza et al…”
Section: Suggested Future Workmentioning
confidence: 99%
“…Due to the limited information presented by Georg and Yakushin, the data presented in these papers was not suitable for comparison in the present work. Recent work by Schott et al 168 consist of radiative intensity measurements at the stagnation point of an ablating model in an arcjet facility. This preliminary work shows promise but has not yet published quantitative results that would allow consideration in the present uncertainty assessment.…”
Section: Past Radiation Measurements With Ablationmentioning
confidence: 99%
“…These have been attributed to ionized calcium (Ca + ) in a similar arcjet experiment where PICA was tested. 12 However other species have emission lines at these same wavelengths such as iron (Fe) at 393.0, hydrogen (H) at 397.0. A weak emission line also appears near 656.3 nm, where the strongest H line is expected.…”
Section: B Flow Over Pica Test Sample 1 Species Identificationmentioning
confidence: 99%